Synthesis and anti-HSV activity of tricyclic penciclovir and hydroxybutylguanine derivatives. Issue 6 (15th March 2019) - Mohammed, Anber F.; Andrei, Graciela; Hayallah, Alaa M.; Abdel-Moty, Samia G.; Snoeck, Robert; Simons, Claire
Graphical abstract: Abstract: A series of tricyclic penciclovir (PCV) and hydroxybutylguanine (HBG) derivatives have been prepared with enhanced lipophilicity following an efficient synthetic route. All the novel tricyclic derivatives were evaluated for inhibitory activity against herpes simplex virus 1 and 2 (HSV-1, HSV-2) and thymidine kinase deficient (ACV resistant) HSV-1. The tricyclic HBG derivatives were devoid of inhibitory activity however several of the tricyclic PCV derivatives showed promising antiviral activity, in particular9g (R = 4-MeO-C6 H4 ) displayed good inhibitory activity (HSV-1 EC50 1.5 μM, HSV-2 EC50 0.8 μM) and retained inhibitory activity in HSV-1 TK − cells (EC50 0.8 μM). Computational docking experiments supported the biological data observed and this preliminary study provides useful data for further development of tricyclic acyclic nucleoside derivatives with improved lipophilicity and retention of activity in HSV-1 TK deficient strains. Also, the new tricyclic derivatives were evaluated against a broad range of other DNA and RNA viruses, but were found to be inactive at subtoxic concentrations. In addition, weak to moderate cytostatic effect was observed for the new compounds.